The evaluation of endothelin-1 and endothelin receptor type a gene polymorphisms in patients with vitiligo - Ilknur Bingül; Ikbal Esen Aydingöz; Pervin Vural; Semra Dogru-Abbasoglu; Müjdat Uysal (Wolters Kluwer Medknow Publications, 2016)
Background: Endothelin-1 (EDN1) and EDN receptor type A (EDNRA) are implicated in melanocyte functions. Aim and Objectives: This study examines the role of EDN1 (G5665T and T-1370G) and EDNRA (C + 70G and G-231A) polymorphisms as a risk factor for vitiligo, and evaluates the relationship between genotypes and clinical characteristics of vitiligo patients. Materials and Methods: We analyzed genotype/allele distributions of EDN1 and EDNRA polymorphisms in 100 patients with vitiligo and 185 healthy controls by real-time polymerase chain reaction. Results: There was no notable risk for vitiligo afflicted by studied polymorphisms. However, the presence of EDNRA +70 variant G allele was found to be related with decreased risk for development of generalized type of vitiligo (odds ratio [OR]: 0.42, 95% confidence interval [CI] = 0.21-0.86, p corr = 0.03) and showed protective effect against associated diseases seen in vitiligo (OR: 0.49, 95% CI = 0.27-0.88, p corr = 0.034). Haplotype analysis demonstrated a strong (disequilibrium coefficient = 0.73, r2 = 0.405) linkage disequilibrium between EDN1 G5665T and T-1370G polymorphisms. The EDN1 5665/-1330 TT haplotype was over represented significantly in controls than in patients (P = 0.04). Conclusion: The studied polymorphisms do not seem to be a major risk for vitiligo. Haplotype analysis denoting protective effects against vitiligo may indicate an indirect interaction in the course of vitiligo. In addition, EDNRA + 70 polymorphism is protective against generalized type of vitiligo and associated diseases.